(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
يدور البحث حول سلطان أو سلطة العلة بصفتها تمثل وجهاً من وجوه الحداثة, التي يظهر فيها وجود الوجود في الفلسفة التي هي مرآة الوجود. يبدأ البحث بتعريفات مبدأ العلة: لا شيء يوجد بلا علة أو بلا شيء يعلل وجوده، وتعريف مصطلحاته، بعد أن تم اكتشافه من قبل لايبنتز ورفعه الى مرتبة المبدأ الأعظم، ليكون أحد أشكال الظهور، وان يشرح الكيفية التي تمثل فيها فهم هايدغر لفلسفة لايبنتز، على أنه يمهد للحداثة ويؤصلها بمبدأ العلة الذي منه وعبره ينبثق الوجود، الذي يصبح مع العقل شيئاً واحداً يذهب بنا الى التيه أو الهاوية حيث يتحول الى المنطق، الى الكومبيوتر, الى قنبلة تهدد وجود الانسان الذي أنتجها خلسة عن نفسه. إذا كان التدمير يطال الحضارة الغربية، فلا نستطيع نحن الهروب من هذا النزوع لأننا نعيش على ضفاف تلك الحضارة. ولكن ألا يسعفنا تراثنا في الاقدام على قفزة نحو الأمام، تبدد حضور الغرب فينا عبر حضورنا في ما تأسس عليه هذا الحضور؟ This article is about the hold or power of reason as an aspect of modernity, in which the existence of being is manifested in philosophy, which is considered the mirror of being. The research starts with definitions of the principle of reason: nothing exists without a reason, or without that which justifies its being and defines its terms. This was discovered by Leibniz and transcended to the rank of supreme principle to be a form of manifestation. It explains how Heidegger understood Leibniz’s philosophy that paved the way for Modernity and grounded it on the principle of reason which emerges from and through being and becomes one thing with the mind, taking us to arrogance or the abyss, when it turns into logic, computer, and a bomb endangering the being of man who produces it in a self deceiving way. If the destruction reaches Western civilization, we cannot run away from this tendency because we live on the sides of this civilization. But can’t our heritage help us to have a leap forward and nullify the presence of the West in us by our own presence in what grounds it?